Hubungan Efek Samping Kemoterapi dengan Kualitas Hidup Pasien Kanker Payudara di Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara - Nasywa Fawwaza; Adi Rizka; Mulyati Sri Rahayu (Pusat riset dan Inovasi Nasional, 2025)
Breast cancer, which typically develops from epithelial cells in the breast ducts or lobes, is a highly prevalent cancer among women worldwide. This disease requires intensive treatment, including chemotherapy, which plays a crucial role in stopping or slowing the growth of cancer cells. Although chemotherapy is effective, it often causes significant side effects, such as nausea, vomiting, fatigue, hair loss, and a weakened immune system. These side effects have the potential to reduce a patient's overall quality of life, both physically, psychologically, and socially. Therefore, this study aims to establish a link between the occurrence of chemotherapy-related side effects and the quality of life of breast cancer patients undergoing treatment at Cut Meutia General Hospital in North Aceh. This study used an observational cross-sectional approach, involving 50 patients undergoing chemotherapy between October and January. Participants were selected purposively to ensure compliance with the study criteria. Data collection was conducted using the Indonesian version of the WHOQOL-BREF, a valid and reliable instrument for measuring quality of life in various domains, including physical, psychological, social, and environmental. Data analysis using the chi-square test revealed a significant relationship between chemotherapy side effects and decreased quality of life in patients with a p-value of 0.002. The results of this study emphasize the need for an adaptive and comprehensive side effect management strategy so that patients can undergo therapy more comfortably and maintain an optimal quality of life during the treatment process. A multidisciplinary approach involving medical personnel, psychologists, and families is highly recommended to support the physical and mental condition of patients during chemotherapy.